2014
DOI: 10.12795/elia.2014.i14.05
|View full text |Cite
|
Sign up to set email alerts
|

English in Finland: Opinions and Attitudes on the Use of Anglicisms

Abstract: As the lingua franca of the moment, English is widely used in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…The obtained results are not in line with previous research on this topic. While some have affirmed positive (e.g., Ćirić-Duvnjak, 2013;Šehović, 2009;Prantl, 2018) and some negative attitudes (e.g., Jódar Sánchez & Tuomainen, 2014;Schreiber, 2006) towards anglicisms, there are rare findings reporting that neutral attitudes have been obtained. The only significant similar findings were obtained by Drljača Margić (2014), who found that Croatian university students hold a neutral attitude toward anglicisms.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results are not in line with previous research on this topic. While some have affirmed positive (e.g., Ćirić-Duvnjak, 2013;Šehović, 2009;Prantl, 2018) and some negative attitudes (e.g., Jódar Sánchez & Tuomainen, 2014;Schreiber, 2006) towards anglicisms, there are rare findings reporting that neutral attitudes have been obtained. The only significant similar findings were obtained by Drljača Margić (2014), who found that Croatian university students hold a neutral attitude toward anglicisms.…”
Section: Discussionmentioning
confidence: 99%
“…Pese a la existencia de, como se ha mencionado, planes de formación tanto inicial como continua en materia AICLE, se siguen evidenciando ciertas necesidades para el docente (Couto y Bobadilla, 2017;Durán-Martínez, 2018;Durán-Martínez y Beltrán-Llavador, 2016;Mier, 2015). Además, a diferencia de otros países como Finlandia, con uno de los sistemas educativos con mejores resultados, en España, el profesorado, que debe certificar un nivel B1 en la LE antes de graduarse y un B2 para participar en la enseñanza bilingüe (a excepción de la Comunidad de Madrid y Navarra, donde se exige un C1 [Ortega-Martín y Trujillo, 2018]), tampoco dispone del apoyo social que supone que el contenido audiovisual se retransmita en versión original como sí ocurre en los países nórdicos (Jódar y Tuomainen, 2014;Vez, Martínez y Lorenzo, 2012).…”
Section: Formación Del Profesorado Aicle: Estado De La Cuestiónunclassified
“…Number of studies has investigated the relation between technology-driven modern media and English language as a lingua franca. For instance, according to Sánchez and Tuomainen (2014), in Finnish Television programs and magazines advertisements, English language is used as an input which is available and can be seen frequently. For a digital game aspect, Piirainen-Marsh (2009) indicated that digital games are the contexts where Finnish children can get the opportunity to the English language exposure as using English can symbolize internationality and trendiness and also shows the expertise in gaming.…”
Section: A Digital Game As An Out Of Class Activity and Autonomous Le...mentioning
confidence: 99%